The Concept of Big Data Analysis for Maritime Information on Indonesian Waters using K-Means Algorithm - Bita Parga Zen (Journal of INISTA, 2021)
Abstract— Indonesia as an archipelagic country has a strategic geographical location, which is located between two continents and two oceans so that it has many advantages, especially in the maritime sector. Indonesia has a goal of becoming a World Maritime Axis that is responsible for ensuring the security and safety of services based on UNCLO S 1982. One way to achieve this goal is to process Big Data to produce useful maritime information . Data can be obtained from government agencies and international organizations and processed according to big data analytics so that it can be visualized information that can be used by various related parties. The collected data can be clustered using the K-Means algorithm with the aim of dividing the data into several groups. This is especially useful for supporting Indonesia based on UNCLOS 1982 by providing information and ensuring the safety of Indonesian waters and being able to contribute to the Indonesian economy.